Reference frames identified through projective prepositions - Aurélie Barnabé (Corela)
English uses the relative Reference Frame (rf) which includes the speaker’s viewpoint assigning directions to identify a Located Object (lo) and a Reference Object (ro). Projective prepositions express the position of the LO and the RO along the front-back and left-right axes: the speaker’s egocentric axes are either mapped onto the RO under a 180-degree rotation so that the speaker’s right is the listener’s left; or the speaker’s egocentric axes are translated onto the RO without rotation. When the RO is a non-fronted object (e.g. a ball), English refers to it without rotation along the left-right axis, but it depicts it with rotation along the front-back line. In comparison to this model, this paper explores the way English treats the location of a RO represented by animate and human entities. The use of projective prepositions to consider animate, fronted items used as RO is here examined through spoken corpora collected with English-speaking students, describing the position of such items with or without rotation.